The Resilience and Preparedness of Nurses in Disasters - Hasena, Siti Luthfiana; Winarti, Wiwin (Universitas Pendidikan Indonesia, 2023)
Introduction: Indonesia's vulnerability to disasters highlights the urgent need for efficient disaster response. While nurses play a pivotal role, there exists a notable gap in their preparedness and the influence of resilience on their readiness. Purpose: This study aimed to investigate the relationship between resilience and disaster preparedness among nurses, exploring how various resilience dimensions impact their readiness for disaster. Methods: Between April and June 2023, 260 nurses from two naval hospitals in Jakarta were surveyed in a cross-sectional study. Participants were selected based on quota sampling and required a permanent registered nurse and minimum nursing diploma. The study utilized the Disaster Adaptation Resilience Scale (DARS) and the Disaster Preparedness Evaluation Tool (DPET) for data collection, analyzed using SPSS v26.0. Variables were categorized as low, medium, or high, with the Chi-Square and Fisher exact test evaluating variable relationships. Results: Of the 260 surveyed nurses, most were female diploma holders over 40 years of age, with over 11 years of experience. The average resilience score was 336.16 (SD=26.575). Resilience sub-components: Physical resources at 41.57 (SD=4.091) and social resources at 37.37 (SD=3.671). Disaster preparedness averaged 218.18 (SD=24.238). The total Resilience was significantly correlated with Disaster Preparedness (p=0.000, OR=0.323). Each resilience dimension was consistently aligned with the heightened disaster preparedness levels. Conclusion: The correlation between resilience and readiness emphasizes the need for holistic nursing training and revised policies to bolster crisis responses.